An English geography curriculum abroad: Using 'third space' as an ideal type to understand similarity and difference. (December 2016) - Chapman, Kay
Where there is a demand for English-medium schooling and English academic qualifications in a former British colony such as Sri Lanka, questions about power relations and the construction of knowledge are raised. Geography is a school subject that claims to make sense of the world. In this article I propose a postcolonial theoretical framework and the concept of third space as an ideal type to compare with interaction in the pedagogical third space of geography classrooms where the syllabus is from a colonial epistemology, teachers may be local or British expatriate and pupils are from affluent families desirous of an English education. This comparison will help further our understanding of how and what kind of geographical knowledge of difference and similarity is constructed through interaction between the syllabus, pupils and teachers in geography classrooms in British international schools.